Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1080/02673843.2004.9747935
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Teacher-Parent-Peer Support on Students' Well-being and Adjustment to the Middle Years of Schooling

Abstract: This report is based on selected data gathered as part of an international project with 2968 South Australian and 5377 Japanese students (10 to 15 years of age). Comparisons between the two countries highlight similarities in the different levels of perceived support from teachers, parents and peers as students progress through the lower to higher year levels at school. The focus of the analyses presented here is on the link between support from teachers and the well-being of students, while the project also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 20 publications
2
18
0
3
Order By: Relevance
“…For lifetime marijuana use, positive student-teacher interaction attenuated risk. This finding reflects the importance of extrafamilial support during adolescence [17,18] and suggests that one strategy to lower risky substance use in adolescence is to foster strong, positive bonds between adolescents and their teachers.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…For lifetime marijuana use, positive student-teacher interaction attenuated risk. This finding reflects the importance of extrafamilial support during adolescence [17,18] and suggests that one strategy to lower risky substance use in adolescence is to foster strong, positive bonds between adolescents and their teachers.…”
Section: Discussionmentioning
confidence: 66%
“…Work by Renick et al [17] using data from the National Longitudinal Study of Adolescent Health (Add Health) has shown that feeling cared for and connected to parents is highly protective against adolescent substance use. Finally, teachers can be a tremendous source of support for adolescents [17,18], particularly when adolescents lack support from parents. Teachers can provide a nonjudgmental point of view, can help adolescents feel connected to school, and can buffer negative interactions with peers.…”
mentioning
confidence: 98%
“…A positive relationship with adults such as teachers is a significant protective factor for at-risk youth (Masten, 2001). TSR is important to facilitate positive peer relationships and to promote student well-being (Cattley, 2004;Schall, Wallace, & Chhuon, 2014). Recent research has also found an association between TSR, student mental health and upper secondary school dropout .…”
Section: Teacher Student Relationshipmentioning
confidence: 99%
“…Less often and usually separately investigated, is the role of teachers in increasing or reducing the incidence of bullying and victimization. The effects of the supportiveness or stressfulness of the student-teacher relationship on students' learning and well-being has been reported extensively in research covering the early childhood years (Birch and Ladd, 1997;Pianta, 1994;Pollard and Davidson, 2001), and in several recent studies covering early adolescence (Cattley, 2004;Klem and Connell, 2004;Murray-Harvey and Slee, 2007;Wentzel, 2002;Wong et al, 2002). Research has identified that females and males (see Rowe, 2002) and younger and older students differ in their experience of school, particularly in terms of relationships with teachers.…”
Section: Introductionmentioning
confidence: 99%